Cevaplar

2013-01-11T12:12:29+02:00

saminin yaşı:x   alinin yaşı:y olsun  x+y=4(x-y)     3yıl sonra= (x+3+y+3)=5{(x+3)-(y+3)}

x+y=4x-4y            y'i yerine koyarsak    x+9=4x-36         -3x=-45    x=15

x+y+6=5x-5y                                                                                         ------

-----------------

2x+2y+6=9x-9y     6+11y=7x     11y-7x=-6

-3\11y-7x=-6     -33y+21x=18

7\5y-3x=0           35y-21x=0

                             --------------

                           2y=18    y=9         

1 5 1